TRANSITIF KLOSUR DARI GABUNGAN DUA RELASI EKUIVALENSI PADA SUATU HIMPUNAN DENGAN STRUKTUR DATA DINAMIS - Endah, Sukmawati Nur (MATEMATIKA, 2005)
A relation R on set A is an equivalence relation on A if and only if R is reflexive, symmetric and transitive. If two equivalence relations on set A areÂ  combined, the combination of them is not surely an equivalence relation, because it is not surely transitive relation. In this paper is found the smallest transitive relation (transitive closure) of the combination, to be an equivalence relation. Then the steps to determine transitive closure are programmed in Pascal programming language with dynamic data structure that is multilist.